Electrochemical polymerization of EDOT modified Phthalocyanines and their applications as electrochromic materials with green coloration, and strong absorption in the Near-IR. (20th September 2016) - Solis, Claudia; Baigorria, Estefanía; Milanesio, María Elisa; Morales, Gustavo; Durantini, Edgardo N.; Otero, Luis; Gervaldo, Miguel
Graphical abstract: Highlights: EDOT substituted phthalocyanines were electropolymerized on Pt, ITO and PEDOT. The films were cycled several times, showing a high electrochemical stability. The films showed green and dark grey colorations, and absorptions in the NIR. A window-type electrochromic device was constructed. Abstract: Electropolymerization by cyclic voltammetry of both Cu and Zn EDOT modified phthalocyanines is described. Polymeric films were successfully formed on Pt, ITO, and Pt containing a previously deposited layer of PEDOT. Based on electrochemical and spectroelectrochemical studies, a possible polymerization mechanism and a polymer structure are proposed. The films showed a green coloration in the reduced state and a grey coloration and also a very broad band that extends to the NIR zone in the fully oxidized state. Optical contrast ratios of 24% at 650 nm, and of 60% at 1050 nm were achieved, with very fast switching times. A window-type device was also constructed, demonstrating the possible applications of these electrochromic materials in smart windows, which could help in the control of light in the visible and in the control of heat flux because of their strong absorption in the NIR range.